2014
DOI: 10.1111/apha.12378
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of transient receptor potential vanilloid 1 in simvastatin‐induced activation of endothelial nitric oxide synthase and angiogenesis

Abstract: Aims: We investigated the role of transient receptor potential vanilloid receptor type 1 (TRPV1) in simvastatin-mediated activation of endothelial nitric oxide synthase (eNOS) and angiogenesis. Methods: Fluo-8 NW assay was for Ca 2+ detection; Griess's assay was for NO bioavailability; Western blotting and immunoprecipitation were for protein phosphorylation and interaction; tube formation and Matrigel plug assay were for angiogenesis. Results: In endothelial cells (ECs), treatment with simvastatin time-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 40 publications
5
57
2
Order By: Relevance
“…TRP channels, as Ca 2+ -permeable channels, play a beneficial role in cardiovascular diseases. Moreover, the TRPV1 channel has been included in the activation of eNOS in several previous studies (40)(41)(42)(43). The present study demonstrated that TRPV1 overexpression increased the phosphorylation of eNOS in the myocardium from isoproterenol-treated mice.…”
Section: Discussionsupporting
confidence: 70%
“…TRP channels, as Ca 2+ -permeable channels, play a beneficial role in cardiovascular diseases. Moreover, the TRPV1 channel has been included in the activation of eNOS in several previous studies (40)(41)(42)(43). The present study demonstrated that TRPV1 overexpression increased the phosphorylation of eNOS in the myocardium from isoproterenol-treated mice.…”
Section: Discussionsupporting
confidence: 70%
“…Treatment with statins promotes angiogenesis in ischemic limbs of normocholesterolemic animals 3. At cellular and molecular levels, simvastatin increases endothelial nitric oxide (eNOS) activity and leads to NO production in endothelial cells (ECs) by regulating a kinase‐dependent pathway and protein‐protein interaction 6, 7. Despite many achievements of statins in treating cardiovascular complications,3, 8, 9, 10 such treatment is not always effective in improving EC function and inflammation, with unclear mechanisms under some circumstances 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of endothelial nitric oxide synthase (eNOS) depends on the formation of calcium-calmodulin complex (Su et al, 2014). However, eNOS can also be activated by phosphorylation with PI3K, a calcium-independent mechanism (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%